Effects of traditional preparatory techniques on the chemical and pasting characteristics of yellow-fleshed cassava roots (Manihot esculenta) - Alamu, E.O.; Maziya-Dixon, B.; Dixon, A. (Oxford University Press, 2023)
Understanding the interactions between chemical and pasting properties and conventional cooking methods will help utilise yellow-fleshed cassava roots. Thus, the study examined how conventional processing affected Nigerian yellow-fleshed cassava's chemical and pasting properties. Three improved, yellow-fleshed genotypes were harvested 12 months after planting: 01/1371 (high carotenoids, 7.3 μg/g on Fresh weight basis (FW)), 01/1235 (medium, 4.8 μg/g FW), and 94/0006 (low, 2.6 μg/g FW). The peeled and washed roots were processed into various products, and chemical and pasting properties were tested. Processing techniques affect all chemical and pasting properties except pasting temperature. High-carotenoid cassava produced boiled roots with high ash and protein, while low-carotenoids produced amylose and starch. High-carotenoid cassava roots yielded flour with high ash, amylose, and starch. The gari product from high-carotenoid cassava roots had higher ash, amylose, sugar, and starch concentrations. Cooked fufu from low-carotenoid cassava had high protein and starch, while high-carotenoid fufu had high ash and amylose. High-carotenoid cassava roots produce the best flour and raw fufu, while low-carotenoid roots produce chips, and medium-carotenoid roots produce gari with suitable pasting parameters.